2010
DOI: 10.1007/s10529-010-0368-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel, thermostable manganese-containing superoxide dismutase from Bacillus licheniformis

Abstract: A new, thermostable superoxide dismutase (SOD) from Bacillus licheniformis M20, isolated from Bulgarian mineral springs, was purified 11-fold with 11% recovery of activity. From native PAGE and SDS-PAGE, the enzyme was composed of two subunits of 21.5 kDa each. The SOD was inhibited only by NaN(3), which suggested that this SOD is of the manganese superoxide dismutase type. The purified enzyme had maximum activity at pH 8 and 55°C. The half-life of the SOD was 10 min at 95°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Even at 80°C, SOD NG2215 remained 52% active after 10 min and almost maintained at this level until 60 min. SOD r , the NTD fused SODA BSn5 , also exhibited good thermostability (retained 80% and 61% active at 50°C and 60°C, respectively, after 60 min), indicating that this enzyme acted more like a moderate thermophilic Mn-SOD from B. licheniformis 20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even at 80°C, SOD NG2215 remained 52% active after 10 min and almost maintained at this level until 60 min. SOD r , the NTD fused SODA BSn5 , also exhibited good thermostability (retained 80% and 61% active at 50°C and 60°C, respectively, after 60 min), indicating that this enzyme acted more like a moderate thermophilic Mn-SOD from B. licheniformis 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Fortunately, the isolation of thermostable SODs from thermotolerant or thermophilic microorganisms offers a rapid and effective means to address this issue. To date, many thermostable SODs have been identified from thermophiles and hyperthermophiles, such as Aquifex pyrophilus 13 , Sulfolobus solfataricus 14 , Aeropyrum pernix 15 , Pyrobaculum aerophilum 16 , Bacillus stearothermophilus 17 , Chloroflexus aurantiacus 18 , Thermomyces lanuginosus 19 , Bacillus licheniformis 20 , Chaetomium thermophilum 21 , and Thermus thermophilus 22 . Recent efforts to improve the thermal resistance of SODs through chemical modification, gene recombination, and simulated SOD compounds have achieved considerable success 23 24 .…”
mentioning
confidence: 99%
“…Among bacterial SODs, the present demand of medical, pharmaceutical and cosmetics industry is thermostable SODs as the production processes involve high temperature and stability is lost. Researchers have tried to explore thermostable SODs and some have achieved success (Boyadzhieva et al, 2010) but no attempt has been made for production process optimization for bulk recovery of enzyme. In the present piece of work, natural thermal habitat, i.e., hot water springs of Himalayan region have been explored for thermostable SOD.…”
Section: Discussionmentioning
confidence: 99%
“…40 The thermal stability of enzymes is a desirable feature for industrial applications that require high temperatures to develop products. 41 In species adapted to different thermal regimes, the kinetic properties of enzymes are typically correlated with environmental temperatures, but the correlation between adaptation temperature and enzyme thermal stability is less clear. 42 Studies on coldadapted enzymes revealed higher structural flexibility, which can accommodate the substrate and transport the enzyme into the activated state with minimum loss of energy.…”
Section: Discussionmentioning
confidence: 99%